Clinical trial of an air-circulating cooling blanket for fever control in critically ill neurologic patients. - Mayer, S; Commichau, C; Scarmeas, N.; Presciutti, M; Bates, J; Copeland, D (Neurology, 2001)
OBJECTIVE: To evaluate the efficacy of an air-circulating cooling blanket for reducing body temperature in febrile neuro-ICU patients treated with acetaminophen. METHODS: Two-hundred twenty consecutively admitted neuro-ICU patients whose tympanic membrane temperature reached or exceeded 101 degrees F (38.3 degrees C) were randomly assigned to receive acetaminophen (650 mg every 4 hours) alone (n = 107) or acetaminophen plus air blanket therapy (n = 113). After 24 hours of treatment, the authors compared the proportion of subjects who attained treatment success (T < or = 99 degrees F) or treatment failure (T > or = 101 degrees F for 2 consecutive hours) using the chi(2) test and the time to reach these endpoints using Kaplan-Meier survival analysis. MAIN RESULTS: Air blanket therapy resulted in a small increase in the proportion of subjects with treatment success (44% versus 36%, chi(2) p = 0.19, log rank p = 0.10) and a similar small reduction in the proportion of patients with treatment failure (42% versus 53%, chi(2) p = 0.11, log-rank p = 0.21), compared with treatment with acetaminophen alone. Approximately one third of patients in both groups remained febrile after randomization and "failed" after the first 2 hours of treatment. Twelve percent of patients assigned to air blanket therapy refused or were unable to tolerate treatment, compared with 2% of patients treated with acetaminophen alone (p = 0.005). CONCLUSIONS: Treatment with an air-circulating cooling blanket did not effectively reduce body temperature in febrile neuro-ICU patients treated with acetaminophen. More effective interventions are needed to maintain normothermia in patients at risk for fever-related brain damage.
Keywords: Adult; Aged; Bedding and Linens; Body Temperature; Body Temperature Regulation; Cryotherapy; Female; Fever; Humans; Male; Middle Aged; Nervous System Diseases